THD performance of single phase five level inverter using proportional resonant and harmonic compensators current controller - Abdullahi Mohamed; Suriana Salimin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper observe the total harmonic distortion (THD) performance of single phase five level inverter using proportional resonant (PR) and harmonic compensators current controller. The THD when adding PR current controller was 1.6% at first. After more functions were added to the PR current controller to reduce the THD at the 3rd, 5th and 7th harmonic orders, the THD of the 3rd harmonic order was reduced from 0.45% to 0.1% while the 5th and 7th harmonic orders were reduced from 0.6% and 0.43% to 0.25% and 0.4% respectively. The development and simulation is performed using Matlab/Simulink. The simulation result is performed by using Fast Fourier Transform analysis (FFT) for the harmonics captured.